KOMPETENSI APARATUR DAN SISTEM PENGENDALIAN INTERNAL PADA PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA - Vidya Vitta Adhivinna; Mega Selawati; M. Sulkhanul Umam (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
The purpose of this research is to detect, examine, and explain the effect of apparatus competence and internal control system on fraud prevention of the villages fund management in the village government of Sentolo Subdistrict Kulon Progo Regency. The research was conducted at 8 Village Government in Sentolo Subdistrict Kulon Progo Regency. The sampling technique in this research was purposive sampling with many respondents 101 village apparatus who were involved in the village fund management in Sentolo Subdistrict Kulon Progo Regency. The data source used was primary data with questuionnaires distributed to the respondents. Multiple regression analysis with the SPSS programmer version 21 is the technique of data analysis. The research results with t test indicated that the variable of apparatus competence (significant value 0,556) do not have an impact on fraud prevention in village fund management. On the other hand, variable of internal control system (significant value 0,000) have an effect on fraud prevention in village fund management. The results of the F test were large 34,410 and the coefficient of determined were large 0,401.